Derivatives

Calculus Level 3

If y = 1 + x 1 ! + x 2 2 ! + x 3 3 ! + + x n n ! y = 1 + \dfrac x{1!} + \dfrac {x^2}{2!} + \dfrac {x^3}{3!} + \cdots + \dfrac{ x^n}{n!} , then find the value of d y d x y + x n n ! \dfrac{dy}{dx} - y + \dfrac{x^n}{n!} .


The answer is 0.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Deepanshu Dhruw
Jan 13, 2017

Since the answer does not depend on n n we can make n n tend to \infty

So we have

y = 0 x r r ! y= \sum_{0}^{\infty} \frac{x^{r}}{r!} as n n\to \infty

So

y = e x y=e^{x} as n n\to\infty

So we have d y d x = e x \frac{dy}{dx} = e^{x} as n n\to \infty

Also we have x n n ! 0 \frac{x^{n}}{n!} \to 0 as n n\to \infty

To prove that we can use Stirling's Approximation

Or a simple theorem which states that

for a sequence ( x n ) n (x_{n})_{n} for which lim n x n + 1 x n = k \lim_{n\to \infty} \frac{x_{n+1}}{x_{n}} = k , 1 < k < 1 -1<k<1 Then ( x n ) n 0 (x_{n})_{n} \to 0 as n n\to \infty .

So we have d y d x y = e x e x = 0 \frac{dy}{dx} - y = e^{x} - e^{x} = 0 as n n\to \infty .

This would be identically true as the answer does not depend on n .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...